Layered Double Hydroxide Nanomaterials Encapsulating Angelica gigas Nakai Extract for Potential Anticancer Nanomedicine - Kim, Hyoung-Jun; Lee, Gyeong Jin; Choi, Ae-Jin; Kim, Tae-Hyun; Kim, Tae-il; Oh, Jae-Min (Frontiers in Pharmacology, 2018)
We prepared hybrids consisting of Angelica gigas Nakai (AGN) root or flower extract and layered double hydroxide (LDH) for potential anticancer nanomedicine, as decursin species (DS) in AGN are known to have anticancer activity. Dimethylsulfoxide solvent was determined hybridization reaction media, as it has affinity to both AGN and LDH moiety. In order to develop inter-particle spaces in LDH, a reversible dehydration-rehydration, so-called reconstruction route, was applied in AGN-LDH hybridization. Quantitative analyses on AGN-LDH hybrids indicated that the content of DS was 2 times more concentrated in the hybrids than in extract itself. Using X-ray diffraction, FT-IR spectroscopy, scanning electron microscopy, and zeta-potential measurement, we found that AGN extract moiety was incorporated into inter-particle spaces of LDH nanoparticles during the reconstruction reaction. Time-dependent DS release from hybrids at pH 7.4 (physiological condition) and pH 4.5 (lysosomal condition) exhibited a pH-dependent release of extract-incorporated LDH hybrids. An anticancer activity test using HeLa, A549, and HEK293T cells showed that the AGN-LDH hybrid, regardless of extract type, showed enhanced anticancer activity compared with extract alone at an equivalent amount of DS, suggesting a nanomedicine effect of AGN-LDH hybrids.